In vitro anti-platelet aggregation activity of the extracts of Camellia Sinensis - Yadav, Anu; Mendhulkar, Vijay D. (Research in Biotechnology, 2015)
Anti-platelet therapy is now appearing as an advanced tool in the treatment of cardiovascular disorders. One of the oldest and best described drugs exhibiting anti-platelet activity is Aspirin, which is however associated with a large number of side-effects. Dietary supplementation with nutrients rich in antioxidants, like tea (Camellia sinensis), is associated with inhibition of atherogenic modifications to LDL and atherosclerosis. Epidemiological studies suggest that tea consumption is associated with a decreased risk of cardiovascular events. Platelet aggregation is a precipitating event in cardiovascular disease, and tea contains antioxidant polyphenols (like catechins) that are known to decrease platelet aggregation in vitro. In the present study, the effect of tea extract was analyzed on platelet aggregation in blood samples with the objective to study potency of phytoconstituents of C. sinensis as a platelet aggregation inhibitor. The study was conducted using Platelet Aggregometer (turbidimetric method developed by Born, 1962), in platelet rich plasma in response to ADP. Our observation revealed that when aspirin is considered as a positive control for platelet aggregation inhibition, the post dilution concentration of 6.25% exhibits 6% higher effect in inhibition of platelet aggregation as compared to aspirin. The analysis was done with 50%, 25%, 12.5% and 6.25% aqueous tea extract. It should be noted that aspirin is taken only after the occurrence of cardiovascular diseases whereas tea is consumed daily and has no side effects like aspirin. Hence, tea consumption on a daily basis can keep heart diseases at bay without causing any side effects which are common with commercial anti-atherogenic drugs.